Should We Operate on Thoracic Aortic Aneurysm of 5-5.5cm in Bicuspid Aortic Valve Disease Patients? - Monaghan, Katelyn; Orelaru, Felix; Naeem, Aroma; Ahmad, Rana-Armaghan; Wu, Xiaoting; Kim, Karen M; Fukuhara, Shinichi; Patel, Himanshu J; Deeb, G Michael; Yang, Bo (Cardiology and Cardiovascular Medicine, 2021)
Background: This study aims to determine the long-term outcomes and rate of reoperation among BAV patients with aortic diameter of 5-5.5cm who underwent immediate surgical repair versus surveillance. Methods: A total of 148 BAV patients with aortic aneurysm measuring 5-5.5cm were identified between 1993 to 2019. Patients were categorized into two groups: immediately operated (n=89), versus watched group (n=59) i.e., monitored until either symptomatic, aortic diameter ≥ 5.5 cm or operated at surgeons’ discretion/patient preference. Results: Compared to the immediately operated group the watched group had significantly lower proportion of proximal aorta replacement (86% vs 100%). The mean size of proximal thoracic aorta at initial encounter, including aortic root, ascending, and arch, for the watched group was 52.1 ± 1.62mm and 52.6 ± 1.81mm in the immediately operated group, p=0.06. There was no significant difference in 10-year survival between the watched group 94% (95% CI: 79%, 99%) vs immediately operated group 96.5% (95% CI: 86%, 99%), p=0.90. Initial operation rate for the watched group during 10-year follow-up was 85%. The operative mortality in both groups was 0%. The 10-year reoperation rate between groups was similar: 3.5% (95% CI: 0.9%, 9.1%) in the immediately operated group vs 7.7% (95% CI: 2.4%, 17.1%) in the patients who eventually had surgery in the watched group, p= 0.30. Conclusions: Our study showed that the rate of reoperation was similar between groups and survival outcomes were acceptable in observed asymptomatic BAV patients without significant family history and with proximal aortic diameter of 5- 5.5cm.